Exploring the impact of curiosity and sport commitment on creativity among fitness coaches: the mediating role of knowledge-sharing and flow experience - Ying Chen; Bin Chen (PeerJ)
The creativity of fitness coaches is crucial for maintaining the competitiveness of fitness enterprises. This study aimed to explore the factors, mechanisms, and moderating effects influencing the creativity of fitness coaches (n = 732) in Chinese fitness businesses, using partial least squares structural equation modeling (PLS-SEM) analysis. The results indicate that curiosity and sport commitment have a positive impact on knowledge-sharing and flow experience. In addition, knowledge-sharing and flow experience positively influence creativity. Importantly, the curiosity and sport commitment of fitness coaches affect creativity through knowledge-sharing and flow experience. Finally, social media usage positively moderates the relationship between knowledge-sharing and creativity. The findings of this study provide meaningful information and decision-making references for professionals in the fitness industry and academic researchers. Future efforts should emphasize the protection of fitness coaches’ creative achievements, with policymakers encouraged to establish relevant legal frameworks to safeguard innovation within the industry.